Pengaruh Metode Pembelajaran dan Kemampuan Generik Sains Terhadap Hasil Belajar Perhitungan Kimia - Azhar Amsal (JTP - Jurnal Teknologi Pendidikan, 2017)
This Research aims to know the influence of different methods of instructional and science generic capability as well as its interaction to the students’ learning result in learning chemistry calculations at Aceh Besar. This study used 2x2 factorial design. The results: 1) student learning result on learning chemistry calculations higher by applying the question posing rather than question solving methods, 2) there is an interaction between instructional method and science generic capabilities to student learning outcomes on learning chemistry calculations, 3) there is not different for student learning outcomes who has high ability on science generic by applying the question posing or question solving methods, and 4) student learning outcomes has the lower ability of generic science on higher by applying the method of question posing rather than question solving methods.